Targeting Lentiviral Vectors to Antigen-Specific Immunoglobulins - Ziegler, Leslie (Mary Ann Liebert, Inc., 2008)
Gene transfer into B cells by lentivectors can provide an alternative approach to managing B lymphocyte malignancies and autoreactive B cell-mediated autoimmune diseases. These pathogenic B cell populations can be distinguished by their surface expression of monospecific immunoglobulin. Development of a novel vector system to deliver genes to these specific B cells could improve the safety and efficacy of gene therapy. We have developed an efficient method to target lentivectors to monospecific immunoglobulin-expressing cells in vitro and in vivo. We were able to incorporate a model antigen CD20 and a fusogenic protein derived from the Sindbis virus as two distinct molecules into the lentiviral surface. This engineered vector could specifically bind to cells expressing surface immunoglobulin recognizing CD20 (αCD20), resulting in efficient transduction of target cells in a cognate antigen-dependent manner in vitro, and in vivo in a xenografted tumor model. Tumor suppression was observed in vivo, using the engineered lentivector to deliver a suicide gene to a xenografted tumor expressing αCD20. These results show the feasibility of engineering lentivectors to target immunoglobulin-specific cells to deliver a therapeutic effect. Such targeting lentivectors also could potentially be used to genetically mark antigen-specific B cells in vivo to study their B cell biology.